Design of a Textile Antenna with Embed Filtering Capability to Remove Unwanted Frequencies and Interference Inside the Antenna in ISM/Wi-Fi Bands - Chandrakanth, Gurijala; Kumar, M. Pranay (International Journal of Aquatic Research and Environmental Studies, 2026)
This paper presents the design and simulation of a compact, fully textile-based, dual-band filtering antenna (filtenna) for wearable Internet of Things (IoT) and healthcare monitoring applications operating in the ISM (2.4 GHz) and Wi-Fi (5.0 GHz) frequency bands. The proposed design integrates a hybrid Defected Ground Structure (DGS) and Complementary Split Ring Resonator (CSRR) mechanism directly within the antenna structure to achieve intrinsic filtering capability without reliance on external filter components. The DGS is realised by introducing periodic slot defects in the conductive textile ground plane, creating band-stop behaviour through equivalent LC resonance, while the CSRR is embedded in the radiating patch to introduce metamaterial-inspired notch filtering for harmonic rejection. Electromagnetic modelling is performed using MATLAB, employing the Antenna Toolbox, RF Toolbox, and Signal Processing Toolbox to evaluate return loss, bandwidth, gain, VSWR, radiation efficiency, and harmonic suppression characteristics. The proposed filtenna achieves return loss values of −28.6 dB at 2.4 GHz and −24.3 dB at 5.0 GHz, peak gains of 4.82 dBi and 6.14 dBi, radiation efficiencies of 81.3% and 78.6%, and VSWR below 1.2 at both operating bands. Harmonic suppression ratios of 32.4 dB and 41.7 dB are achieved at the second and third harmonics respectively, representing improvements exceeding 26 dB over a conventional textile antenna without embedded filtering. The proposed design addresses the existing research gap in compact, fully flexible, dual-band wearable filtennas operating simultaneously at ISM and Wi-Fi frequencies with inherent interference suppression, making it well-suited for wearable body area network (WBAN) applications in healthcare and IoT domains.
Keywords: Textile antenna, filtenna, Defected Ground Structure, Complementary Split Ring Resonator, dual band, wearable, ISM band, Wi-Fi, harmonic suppression, WBAN.